Disability and Health Consequences of Traumatic Brain Injury: National Prevalence. (May 2018) - Jourdan, Claire; Azouvi, Philippe; Genêt, François; Selly, Nicolas; Josseran, Loic; Schnitzler, Alexis
Abstract : Objective: The aim of the study was to measure the prevalence of traumatic brain injury (TBI)-related disability and health status in the general population. Design: The French National Survey, conducted in households and institutions, assessed 33, 896 adults. Data included sequelae from TBI, impairments, current health conditions, and uses of health services. Analyses, adjusted for age and sex, compared subjects who declared sequelae from TBI ( n = 479) with the remaining survey population ( n = 33, 287). Use of weighting factors ensured that results were representative of the national population. Results: Prevalence of persistent sequelae from TBI in France was 704/100, 000. Median time since injury was 14 yrs. For all Core Set items of the International Classification of Functioning, subjects with TBI reported more impairments than the control population: adjusted odds ratios from 1.7 (behavioral difficulties) to 8.6 (motor difficulties). Rates of cardiovascular, respiratory, musculoskeletal, digestive, urological, neurological, and psychiatric conditions were higher in the TBI population. Use of health services was greater, and women with TBI had higher rates of unmet health needs. Conclusions: Persistent sequelae from TBI significantly affect health in the general population. Planning of post-TBI care should address the chronic needs of these persons. Abstract : Supplemental digital content is available in the text.